Dyonic Taub-NUT-AdS Space Phase Structure - Tharwat, Mohamed (AUC Knowledge Fountain, 2023)
The Taub-NUT spacetime remains to hold many mysteries more than half a century after its discovery. The metric's controversy owes largely to the nut charge and the existence of Misner strings. Traditionally the metric is treated in the euclidean signature, this treatment hides the Misner strings. We treat the Taub-NUT spacetime with the Misner strings visible, not enforcing the time periodicity condition. We examine the phase structure belonging to three different horizon geometries. We deal with the hyperbolic, flat and spherical cases. We consider the stable phases, the phase transitions that exist between them, and find the preferable phases in all three spacetimes.